2003
DOI: 10.1002/bdra.10041
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide‐induced axial skeletal dysmorphogenesis in the chick embryo

Abstract: We hypothesize that the somitic defects and the resulting axial skeletal dysmorphogenesis are caused by disrupted neural tube or ectoderm functions related to somite formation and maintenance. We also hypothesize that CO-induced dysmorphogenesis at this critical period of somitogenesis is caused by the overabundance of CO acting endogenously as a cellular signal, while coincidentally exerting its influence as a toxicant of oxygen delivery or utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…There is a known role for NO in bone [327]. These skeletal defects are comparable to the skeletal anomalies induced in chicken embryos following exposure to CO [328].…”
Section: B the Teratology Of Nomentioning
confidence: 73%
See 2 more Smart Citations
“…There is a known role for NO in bone [327]. These skeletal defects are comparable to the skeletal anomalies induced in chicken embryos following exposure to CO [328].…”
Section: B the Teratology Of Nomentioning
confidence: 73%
“…Additionally, many of the signaling pathways impacted by CO are oxygen-based signaling pathways [362]. However, a comparison of the CO-exposure phenotype with the hypoxia phenotype indicated differences between the two [328]. This suggested that CO disruption of organogenesis was mechanistically distinct from the hypoxic response.…”
Section: The Teratology Of Comentioning
confidence: 82%
See 1 more Smart Citation
“…AVS is a common congenital abnormality that occurs with a prevalence of about 2-3/1000 births [24]. AVS can be divided into two main groups based on the number of vertebrae affected (Figure 2a).…”
Section: Abnormal Vertebral Segmentation In Humansmentioning
confidence: 99%
“…Moreover, maternal smoking is the greatest identified cause of fetal weight deficiency, premature birth, miscarriage, perinatal/ neonatal death, neural tube defects, and congenital anomalies (6)(7)(8)(9)(10)(11). Furthermore, it adversely affects the development of organs and tissues serving several functions in cardiovascular and skeletal systems (12).…”
Section: Introductionmentioning
confidence: 99%